2021
DOI: 10.1007/s10811-021-02638-2
|View full text |Cite
|
Sign up to set email alerts
|

The SeaCoRe system for large scale kelp aquaculture: a plug-and-play, compatible, open-source system for the propagation and transport of clonal gametophyte cultures

Abstract: The future of large-scale kelp aquaculture is standing at a crossroad, with the diverging paths being characterized by two fundamentally different cultivation methods that differ on how well gametophyte reproduction can be controlled. The cultivation method that does not directly control gametophyte reproduction is more widely utilized at the moment, but interest in better controlling gametophyte reproduction is growing steadily. Here, we validate a bioreactor system that overcomes a number of implementation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Thus, this practice could facilitate selective breeding and strain selection akin to traditional methods of terrestrial vegetable production, where seeds from the best performing plants are collected for the following season's plantings (Goecke et al 2020;Hwang and Park 2020). This may avoid some of the problems associated with long-term degeneration in blade quality and productivity due to excessive inbreeding (Liu et al 2014) and consequently reduced genetic diversity reported for aquaculture production of laminarian kelps kept in continuous culture (Liu et al 2012;Shan et al 2016;Alsuwaiyan et al 2021;Ebbing et al 2022). Furthermore, we recommend that initial, small-scale wildharvest and collection of seed stock could be considered ecologically sustainable if timed with peak growth periods, with larger (> 40 cm for C. torulosa and > > 50 cm for C. uvifera) fronds removed where possible to minimise the number of thalli needed to obtain the desired harvested biomass.…”
Section: Knowledge Gaps and Pathways To Commercialisationmentioning
confidence: 99%
“…Thus, this practice could facilitate selective breeding and strain selection akin to traditional methods of terrestrial vegetable production, where seeds from the best performing plants are collected for the following season's plantings (Goecke et al 2020;Hwang and Park 2020). This may avoid some of the problems associated with long-term degeneration in blade quality and productivity due to excessive inbreeding (Liu et al 2014) and consequently reduced genetic diversity reported for aquaculture production of laminarian kelps kept in continuous culture (Liu et al 2012;Shan et al 2016;Alsuwaiyan et al 2021;Ebbing et al 2022). Furthermore, we recommend that initial, small-scale wildharvest and collection of seed stock could be considered ecologically sustainable if timed with peak growth periods, with larger (> 40 cm for C. torulosa and > > 50 cm for C. uvifera) fronds removed where possible to minimise the number of thalli needed to obtain the desired harvested biomass.…”
Section: Knowledge Gaps and Pathways To Commercialisationmentioning
confidence: 99%
“…A considerable amount of research has been undertaken over the recent years to understand the gametophyte biology, development and quality relating to several biotic and abiotic factors, such as age, density, seasonality, sex ratio, light, temperature, and nutrients (Nielsen et al 2016a;Ebbing et al 2020Ebbing et al , 2021aRaymond and Stekoll 2021;Boderskov et al 2022). A bioreactor system that overcomes several implementation challenges for this controlled reproductive method, expanding the possibility of clonal gametophyte cultivation outside of expensive laboratory settings, has been validated (Ebbing et al 2022). This system's three goals include maintaining clean gametophyte clonal cultures in non-sterile environments over prolonged periods, producing large numbers of juvenile sporophytes, and effective transportation of gametophytes and sporophytes.…”
Section: Cultivation Strategies -Nurserymentioning
confidence: 99%
“…With increasing global awareness of the ecological value, economic potential, and anthropogenic threats facing kelps, kelp aquaculture for commercial, conservation, and scientific purposes is becoming increasingly widespread (Ebbing et al., 2022; Eger et al., 2022; Kim et al., 2017; Morris et al., 2020). Typically, kelps are first reared in land‐based “hatcheries” before being outplanted at a small size (<2 cm) to nearshore ocean farms for “growing out” (Azevedo et al., 2016; Flavin et al., 2013).…”
Section: Introductionmentioning
confidence: 99%